2019
DOI: 10.1108/s2516-285320190000002055
|View full text |Cite
|
Sign up to set email alerts
|

Exploitative Learning in Inter-Organizational Projects: Evidence from Dutch Infrastructure Practices

Abstract: Purpose -How learning is facilitated in inter-organizational projects remains underdeveloped in the literature. The aim of this study is to focus on viewing the relationship between the multiple organizations in a project, from a perspective of the learning aspect.Design/Methodology/Approach -This research analyses the learning trajectory that occurred in the largest tunnel project in the Netherlands. Data were collected through archival documents, in-depth interviews, and site visits. Answering the research q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Previous research has shown that exploitative learning leads to unique SME product innovation (Chen et al, 2020;Liu et al, 2021), because ideas cannot be imitated by outsiders. Thus, the success of organizational performance is significantly influenced by optimizing existing knowledge in a stable business environment (Liu et al, 2019;Shafique et al, 2021). According to Tian et al (2021), exploitative learning is also more effective when a business has limited time to produce new items and so requires it to use existing knowledge to improve its business performance.The success of exploitative learning depends on the availability of exploitable capabilities, assets, or resources in the organization, which are under the organization's internal control (Ojha et al, 2018).…”
Section: Literature Review Exploitative Learningmentioning
confidence: 99%
“…Previous research has shown that exploitative learning leads to unique SME product innovation (Chen et al, 2020;Liu et al, 2021), because ideas cannot be imitated by outsiders. Thus, the success of organizational performance is significantly influenced by optimizing existing knowledge in a stable business environment (Liu et al, 2019;Shafique et al, 2021). According to Tian et al (2021), exploitative learning is also more effective when a business has limited time to produce new items and so requires it to use existing knowledge to improve its business performance.The success of exploitative learning depends on the availability of exploitable capabilities, assets, or resources in the organization, which are under the organization's internal control (Ojha et al, 2018).…”
Section: Literature Review Exploitative Learningmentioning
confidence: 99%